ANALISIS TINGKAT KEPUASAN PENGGUNA LANGSUNG DAN TIDAK LANGSUNG TERHADAP APLIKASI SUATU SISTEM INFORMASI - Agus Sulaiman (Business Management Journal, 2017)
Information system is becoming much more important for a company to gain competitive advantage compared to their competitors. A company with good information systems will acquired better opportunity .The purpose of this study is to understand the satisfaction level of an information system application and factors that influenced the user satisfaction. Factors that have been tested are system speed, system security, system accuracy, effectiveness and efficiency, ITSupport and user friendliness. This study was taken place in PT X that uses an IS application to support company business. The result shows that users are satisfied to the current application. There are three factors that significantly influence user satisfaction: system accuracy, system speed, and IT support. On the contrary, factors that have not significantly influencing user satisfaction of information system are system security, effectiveness and efficiency, and user friendly. Some actions must be taken such as repairing system speed from hardware site, software development, and networking reliability.Next module to be developed is Fixed Asset Module, based on the readiness of accounting division.Keywords: information systems, user satisfaction, application